'What does terrorism look like?': university lecturers' interpretations of their Prevent duties and tackling extremism in UK universities. Issue 1 (2nd January 2018) - Spiller, Keith; Awan, Imran; Whiting, Andrew
ABSTRACT: The UK Counter Terrorism and Security Act (2015) (CTSA) calls for a partnership between the government, individuals, organisations and communities to prevent the radicalisation of individuals and to prevent their participation in terrorist and illegal activities. As part of this strategy, universities have a statutory duty placed upon them to remain vigilant to signs of extremism. Based upon 20 interviews with UK university lecturers, the paper examines reactions of the academic community to this governmental mandate. Key to our understanding is the deputisation of lecturers into a security regime and how they perform the duty of identifying and monitoring extremism. Equally, forms of resistance are evident in how lecturers understand their new roles and for universities themselves a conservative approach to risk may be gaining traction. We argue there is confusion around the CTSA based upon the ambiguous language in which it is presented and the conservative and defensive reactions that have subsequently produced concern amongst lecturers and UK universities.